Pengembangan Konsep Agroindustri Berbasis Sistem Usahatani Terpadu di Wilayah Pasang Surut Bagian I: (Konsep Pemikiran) - Rustan Massinai; Putu Sudira; Muhjidin Mawardi; Dwijono Hadi Darwanto (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2013)
Integrated farming system was directed in efforts to lengthen biological cycle by optimizing use of agriculture and livestock products. Each chain of cycle resulted new product that have high economic value, so this system was expected to optimize empowerment and use of marginal land in all regions. The problems encountered in agricultural systems in tidal swamp land in general, i.e; (a) limitations in the form of land, human resources, technology, and capital owned by farmers, then the potential of local resources need to be managed optimally, directed, integrated and sustainable with a view to improve land productivity and living standards of farmers by way of application of integrated farming systems by integrating crop and livestock based on the potential of local areas, and (b) socio-economic problems and constraints in the development of food crops was due to a swamp area. The objective of this research was to produce integrated farming system concept to support agroindustry development in tidal swamp land in Pulang Pisau regency of Central Kalimantan province. This research was conducted with a book study method, which identifies a system consisting of integrated farming and agroindustry systems. In the both identification is performed by the system includes four aspects, i,e; economic aspects, technical aspects, social aspects of cultural and environmental. Integrated farming systems concept in tidal swamp land was generated from the production of integrated farming systems should first be processed through the processing system (agroindustry) in the form of home industry, or using a mechanical device. After that, it was carried out the marketing of products, systems concepts was expected to increase the added value of agricultural production (rice, coffee and cow). With the application of agroindustry systems in tidal swamp land Pulang Pisau regency of Central Kalimantan Province is expected to increase the economic income of farmers in village.ABSTRAKSistem pertanian terpadu diarahkan pada upaya memperpanjang siklus biologis dengan mengoptimalkan pemanfaatan hasil samping pertanian dan peternakan. Setiap mata rantai siklus menghasilkan produk baru yang memiliki nilai ekonomis tinggi, sehingga dengan sistem ini diharapkan pemberdayaan dan pemanfaatan lahan marginal di seluruh daerah dapat lebih dioptimalkan. Permasalahan-permasalahan yang dihadapi dalam sistem pertanian di daerah pasang surut secara umum, yaitu; (a) keterbatasan yang berupa lahan, sumberdaya manusia, teknologi, serta modal yang dimiliki petani, maka potensi sumberdaya lokal perlu kelola secara optimal, terarah, terpadu dan berkelanjutan dengan maksud untuk meningkatkan produktifitas lahan serta taraf hidup petani dengan cara penerapan sistem usahatani terpadu (integrated farming system) dengan mengintegrasikan tanaman dan ternak berdasarkan potensi wilayah setempat, dan (b) masalah dan kendala sosial ekonomi pengembangan tanaman pangan di daerah rawa. Penelitian ini bertujuan untuk menghasilkan konsep pengembangan sistem usahatani terpadu untuk mendukung agroindustri di lahan pasang surut di Kabupaten Pulang Pisau Provinsi Kalimantan Tengah. Penelitian ini dilakukan dengan metode studi pustaka, yaitu mengidentifikasi sistem yang terdiri dari sistem usahatani terpadu dan sistem agroindustri. Dalam identifikasi kedua sistem tersebut dilakukan meliputi empat aspek yaitu, aspek ekonomi, aspek teknis, aspek sosial budaya dan aspek lingkungan. Konsep sistem usahatani terpadu di lahan pasang surut yang dilakukan yaitu hasil produksi yang dihasilkan dari sistem usahatani terpadu hendaknya terlebih dahulu diolah melalui sistem pengolahan (agroindustri) baik berupa industri rumah tangga (home industry) maupun menggunakan alat mekanis, setelah itu dilakukan pemasaran produk, konsep sistem tersebut diharapkan dapat meningkatkan nilai tambah produksi pertanian (padi, kopi dan ternak sapi). Dengan penerapan sistem agroindustri di lahan pasang surut Pulang Pisau Provinsi Kalimantan Tengah diharapkan dapat meningkatkan pendapatan ekonomi petani di pedesaan.